PENGHILANGAN AMONIAK DI DALAM AIR LIMBAH DOMESTIK DENGAN PROSES MOVING BED BIOFILM REACTOR (MBBR) - Said, Nusa Idaman; Syabani, Muhammad Rizki (Jurnal Air Indonesia, 2014)
The treatment process of wastewater contains organic pollutant which used in Indonesia especially in Jakarta is generaly activated sludge process. The problem is its treated water quality which frequently does not yet fulfilled to effluent standard of wastewater. Some affecting factors are hydraulic retention time (HRT) too short, the fluctuation of wastewater flow rate, unfavorable function of aeration process and also which do not less important is operational mistake caused by insufficient knowledge of operator. To overcome the mentioned problems it is needed technological innovation to increase efficiency of wastewater treatment process especially activated sludge process. Moving Bed Biofilm Reactor (MBBR) technology is one of the effective alternative for treating wastewater containing organic pollutants. In principle, MBBR is a modification of the activated sludge process is enhanced by adding the media into the aeration tank.This paper describes the study of domestic waste water treatment using MBBR process which is filled with bioball plastic media which has specific surface 210 m2/m3 as much as 20 % of the volume of the aeration tank for attaching microorganism to increase efficiency and keep stability of process.Result of the study shows that within 12 hours, 8 hours, 6 hours and 4 hours of hydraulic retention time (HRT) in aeration tank and sludge circulation ratio 0f R = 1.0 Q, the removal efficiency of ammonia were 94.05 %, 93.42 %, 89 %, and 79.6 % respectively. In ammonia loading 0.106 – 0.302 kg/m3.day, the removal efficiency of ammonia were 95.54 – 83.01 %. The greater ammonia loading, removal efficiency of ammonia is getting smaller. Optimal residence time is 6 hours with ammonia removal efficiency reached 89 %, and the average concentration of ammonia in the effluent of 8.3 mg per litre. Keyword : Domestic wastewater, ammonia, bioball, MBBR.